An Exploratory Study of Post-Graduate Students’ Perspectives of the Importance of Personal Branding in the Workplace - Robert, Simone (The IIE, 2017)
How one presents oneself online and offline can have repercussions. If young individuals were more aware of this, they would possibly be able to create and control their personal brand and, therefore, increase their chances of acquiring a job. The purpose of this study is to explore post-graduate students’ perceptions of personal branding and the role it plays in today’s workplaces. This research used a qualitative exploratory research approach to gain a deeper understanding of the students’ perceptions of social media and personal branding and how they possibly influence each other. A case study methodology was used as the foundation for collecting the data from a focus group which comprised of 6 participants. Thematic analysis was used to analyse the data, which identified 5 themes: Contextual Factors, Degree of Familiarity, Impressions: Online and Offline Personas, Micromanagement, and Authenticity. It was determined from the research that post-graduate students present themselves consistently online as they do offline because they have learned the importance of creating a unique personal brand. This research was limited in scope and could benefit from enlarging the scale to incorporate post-graduate students studying different degrees to increase the diversity of the responses
Keywords: Personal branding; Online behaviour; Work place skills